2023
DOI: 10.3389/fpsyg.2023.1080550
|View full text |Cite
|
Sign up to set email alerts
|

Association between media exposure and behavioral problems among preschool children

Abstract: BackgroundThe prevalence of behavioral problems among preschool children is remarkably increasing in the clinical setting.AimThe current study aimed to investigate the association between media exposure and behavioral problems among preschool children.MethodsThis survey study recruited 560 children from 10 nurseries selected randomly, located in El-Mansoura, Egypt. Tools included socio-demographic characteristics the Media Exposure Questionnaire and the Conners Comprehensive Behavior Rating Scales (CBRS-48).Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Feng et al have noted potential benefits, such as enhancing spatial attention and reducing gender disparities in spatial cognition through action video games [ 8 ]. Conversely, findings by Zoromba et al suggest that excessive media exposure may be associated with hyperactivity, anxiety, and learning difficulties in children [ 9 ]. Similarly, research by Raheem et al has shown negative correlations between the duration of electronic media exposure and developmental aspects such as attention and language [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al have noted potential benefits, such as enhancing spatial attention and reducing gender disparities in spatial cognition through action video games [ 8 ]. Conversely, findings by Zoromba et al suggest that excessive media exposure may be associated with hyperactivity, anxiety, and learning difficulties in children [ 9 ]. Similarly, research by Raheem et al has shown negative correlations between the duration of electronic media exposure and developmental aspects such as attention and language [ 10 ].…”
Section: Introductionmentioning
confidence: 99%